2006
DOI: 10.1097/00005082-200605000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Therapy on Physiological and Psychological Outcomes for Patients Undergoing Cardiac Surgery

Abstract: Patients recovering from cardiac surgery may benefit from music therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
4
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 21 publications
7
130
4
14
Order By: Relevance
“…A small number of studies followed up patients for multiple hospital days or repeated the interventions over the course of hospitalization. 2,13,14 Many of the studies incorporated some element of patients' choice in selecting the music. Such choice is very important to the success of any music intervention, as choice can enhance daily for 20 to 30 uninterrupted minutes in a comfortable environment and position in bed, encouraging the patient to self-direct how long and frequently he or she would like to listen to preferred music selections.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…A small number of studies followed up patients for multiple hospital days or repeated the interventions over the course of hospitalization. 2,13,14 Many of the studies incorporated some element of patients' choice in selecting the music. Such choice is very important to the success of any music intervention, as choice can enhance daily for 20 to 30 uninterrupted minutes in a comfortable environment and position in bed, encouraging the patient to self-direct how long and frequently he or she would like to listen to preferred music selections.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…Some have indicated that music therapy reduced stress and anxiety in the patients [6][7][8][9][10], but others have found no effect of music intervention on post-procedural pain and anxiety, although music therapy improved the level of comfort in patients [1,11]. Gallagher et al indicated that music therapy is invaluable in palliative medicine [12].…”
Section: Introductionmentioning
confidence: 99%
“…In other study in 2006, Sendelbach et al, examined the effects of music therapy on physiological and psychological outcomes for patients undergoing cardiac surgery. They reported that music have significant effect in reducing pain and anxiety in this group of patients after surgery [25]. Although result of present study and other previous studies showed that music have a positive effect on patient's pain after cardiac surgery however researchers and clinicians should consider patients' culture, music type, music time and time of day that music played.…”
Section: Discussionmentioning
confidence: 43%
“…No difference between the groups in the other physiologic parameters was reported by Özer et al [10]. In other study Sendelbach et al, reported that music have not negative effect on physiological parameter of patients after cardiac surgery [25].…”
Section: Effect Of Listening To Preferred Music On Intensity Of Pain mentioning
confidence: 76%